We Saw Lincoln Shot : One Hundred Eyewitness Accounts - Good, Timothy S. (Timothy Sean) (Book collections on Project MUSE., 1996)
On the evening of 14 April 1865 when President Abraham Lincoln was assassinated in Ford's Theatre, an entire audience was witness to the tragedy. From diaries, letters, depositions, affidavits, and periodicals, here is a collection of accounts from a variety of theatergoers - who by chance saw one of the truly pivotal events in U.S. history. Providing minute first-hand details recorded over a span of ninety years, We Saw Lincoln Shot explores a subject that will forever be debated. With a sharp focus upon the circumstances reported by one hundred actual witnesses, We Saw Lincoln Shot provides.